PENGARUH RETURN ON ASSET DAN CURRENT RATIO TERHADAP DIVIDEND PAYOUT RATIO DI PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nabiya Saski Fadila; Sunartiyo (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
The purpose of this study was to determine The effect of return and current ratio on dividen payour ratio, the effect of return on asset on dividen payour ratio, and the effect of current ratio on dividen payour ratio. This research uses quantitative data analysis technique. Sampling using purposive samping method using certain criteria. The result of this study indicate that return on assets and current ratio have an influence on the dividens payour ratio, return on assets has an influence on the dividens payour ratio, and current ratio has an influence on the dividens payour ratio for the Food and Beverage Sub Sector Companies Registered In Indonesia Stock Exchange